Tragic-Remorse–The Anguish of Dirty Hands - De Wijze, Stephen (Ethical theory and moral practice, 2005)
This paper outlines and defends a notion of ‘tragic-remorse’. This moral emotion properly accompanies those actions that involve unavoidable moral wrongdoing in general and dirty hands scenarios in particular. Tragic-remorse differs both phenomenologically and conceptually from regret, agent-regret and remorse. By recognising the existence of tragic-remorse, we are better able to account for our complex moral reality which at times makes it necessary for good persons to act in ways that although justified leave the agent with a moral stain and a particular emotional response.